Suppressor of cytokine signaling-3 expression and its regulation in relation to inflammation in Chronic Obstructive Pulmonary Disease - Tinè, Mariaenrica; Balestro, Elisabetta; Carpi, Sara; Neri, Tommaso; Biondini, Davide; Conti, Maria; Casara, Alvise; Bernardinello, Nicol; Cocconcelli, Elisabetta; Turato, Graziella; Baraldo, Simonetta; Celi, Alessandro; et al. (Frontiers in Immunology, 2024)
Background The family of Suppressor of Cytokine Signaling (SOCS) acts as a controller of the duration and intensity of cytokine function by negatively regulating the JAK-STAT signaling pathway. SOCS’ role in inflammatory diseases in animal models is well demonstrated. However, its role in the development of human disease is still under investigation. SOCS3 plays an important role in tumor development where its downregulation has been implicated in the pathogenesis of various solid tumors such as triple-negative breast cancer. Aim The aim of this work was to study (1) the expression of SOCS3 in smokers’ lungs and its relation to the degree of inflammation and (2) SOCS3 regulation by microRNA (miRNA) in alveolar-macrophage (AM)-derived extracellular vesicles (EVs) in bronchoalveolar lavage (BAL). Methods Group A: 35 smokers’ [19 with COPD (SC) and 16 without COPD (S)] and 9 nonsmokers (NS); SOCS3, TNFα in AM, and CD8+ T cells were quantified by immunohistochemistry, in lung tissue. Group B: additional 9 SC, 11 S, and 5 NS; AM-EVs expressing SOCS3 (CD14+SOCS3+) and SOCS3 suppressors miRNA-19a-3p and 221-3p in EVs were quantified by flow cytometry and PCR, in BAL. Results The percentage of SOCS3+ AM was higher in SC [68 (6.6–99)%] and S [48 (8–100)%] than in NS [9.6 (1.9–61)%; p = 0.002; p = 0.03] and correlated with % of TNFα+AM (r = 0.48; p = 0.0009) and CD8+ T cells (r = 0.44; p = 0.0029). In BAL, the CD14+SOCS3+ EVs/μL were increased in SC [33 (21–74)] compared to S [16 (8–37); p = 0.03] and NS [9 (7–21); p = 0.003]. Conversely, miRNA-19a-3p and miRNA-221-3p expression were increased in S when compared to SC [19 (2–53) vs. 3 (0.6–8); p = 0.03 and 3 (0.005–9.6) vs. 0.2 (0.08–0.7); p = 0.05]. Conclusions The suppressor function of SOCS3 in COPD seems to be overridden by other factors and does not follow the animal-model paradigm. Expression of SOCS3 in BAL macrophage-derived EVs might be useful to assess the degree of inflammation and possible progression of COPD. Downregulation of SOCS3, by miRNA, in smokers without COPD might contribute to the risk of developing cancer in these patients.